Sustainable strategies applied to supply chains: a literature review - Del Rosso Calache, Lucas Daniel [UNESP]; Bertassini, Ana Carolina; Osiro, Lauro; Carpinetti, Luiz Cesar Ribeiro (Inderscience Publishers, 2024)
Sustainability in the supply chain becomes strategic for organisations because social pressure has increased about environmental and human rights issues, supply chain risks have become more relevant, and laws about packing and end-of-life products toughened up. Over the years, studies about sustainable supply chain development have increased, in the most varied organisational contexts, but none of the studies present a review of the papers that address sustainable strategic decisions in supply chain issues. Therefore, this study aims to identify the sustainable strategies and strategic actions used in supply chains. A systematic literature review was used as a method to accomplish the research goal. The results highlight the state of the art since the analysed papers were classified according to the research method, year of publication, country, application field, multi-criteria technique applied, sustainable strategies used, and type of data collected. Besides, some opportunities for future studies in the subject are presented.
Keywords: decision making; multi-criteria techniques; supply chain; sustainable strategies; systematic literature review